2017
DOI: 10.1111/ijal.12165
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceptual salience in the L2 acquisition sequence of the Arabic construct state

Abstract: Perceptual salience has been proposed as an essential factor in the order in which various linguistic phenomena are acquired. This study examines its influence on the acquisition sequence of a single construction, which is the Arabic construct state. Mapping certain English constructions to the definite Arabic construct state entails restructuring head direction (a feature of high salience) and the position of the definite marker (a feature of low salience). Results from a prompted sentence completion task sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…rigid) left-headedness in Arabic construct phrases contributed to its perceptual salience that minimized transfer of the right-headed s -genitives from English to Standard Arabic. Results of the present study, when seen in light of the results of Azaz and Frank (2017), show that once the conditions of the structural overlap are met, crosslinguistic transfer is most likely to occur from the rigid to the optional language, and less likely from the optional to the rigid. This suggests that input conditions, whether ambiguous or transparent, are crucial.…”
Section: Discussionmentioning
confidence: 50%
“…rigid) left-headedness in Arabic construct phrases contributed to its perceptual salience that minimized transfer of the right-headed s -genitives from English to Standard Arabic. Results of the present study, when seen in light of the results of Azaz and Frank (2017), show that once the conditions of the structural overlap are met, crosslinguistic transfer is most likely to occur from the rigid to the optional language, and less likely from the optional to the rigid. This suggests that input conditions, whether ambiguous or transparent, are crucial.…”
Section: Discussionmentioning
confidence: 50%
“…According to Azaz and Frank (2017), i d aafa, or the CS, can be defined as a relationship between two nouns annexed together. The first noun is the head whereas the second noun is the complement.…”
Section: General Backgroundmentioning
confidence: 99%
“…The analysis of the study revealed that while the participants showed metalinguistic knowledge of head-direction, they did not demonstrate the same comparable knowledge for definiteness. Azaz and Frank (2017) also examined the role of perceptual salience in the acquisition sequence of the Arabic construct state. They specifically studied whether salience regulates the early L2 acquisition sequence of the definite Arabic construct state.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to consider is the importance of linguistic salience in the development of L2 knowledge of grammatical properties/features (Azaz, 2017; Azaz & Frank, 2017; Nassif, 2019; Xu & Lyster, 2014). As Azaz (2017) stated, in the course of the acquisition of salient features which are easy to notice in the input, metalinguistic knowledge plays an important role, suggesting the relevance of explicit instruction in the development of the features which are of low salience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation